2018
DOI: 10.1186/s40345-017-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antithyroid antibodies contribute to the decrease of glomerular filtration rate in lithium-treated patients: a longitudinal study

Abstract: BackgroundConcerns about the adverse effects of long-term treatment with lithium include reduced renal function. In the present study, we examined comorbidities which may be associated with chronic kidney disease in a cohort of patients treated with lithium for up to 41 years.MethodsWe studied 394 patients who were treated with lithium for ≥ 5 years. The potential role of comorbidities (diabetes, concurrent antihypertensive medication, treatment with l-thyroxine, and presence of antithyroid peroxidase/microsom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Bocchetta et al. 31 first reported a link between renal function and the presence of thyroid antibodies including TPOAb and TGAb. They studied 394 patients who were treated with lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Bocchetta et al. 31 first reported a link between renal function and the presence of thyroid antibodies including TPOAb and TGAb. They studied 394 patients who were treated with lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Gastro-intestinal complaints may be lessened by switching to another lithium preparation. Hypothyroidism is also possible and usually is treated with supplemental thyroid-hormone (Ambrosiani et al 2018; Bocchetta et al 2018). Hyperparathyroidism and consequent hypercalcemia can also arise during long-term treatment with lithium (Twigt et al 2013).…”
Section: Adverse Effects and Contraindicationsmentioning
confidence: 99%
“…In these patients, the rates per year of newly developed circulating thyroid antibodies and hypothyroidism were 1.7 and 1.5 %, respectively. Recently, Bochcetta et al [11] suggested also that, in lithium-treated patients, circulating antithyroid antibodies can contribute to the decrease of glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 99%